Recognition of soybean pods and yield prediction based on improved deep learning model - He, Haotian; Ma, Xiaodan; Guan, Haiou; Wang, Feiyi; Shen, Panpan (Frontiers in Plant Science, 2023)
As a leaf homologous organ, soybean pods are an essential factor in determining yield and quality of the grain. Thus, a recognition method of Soybean pods and estimation of pods weight per plant were proposed based on improved YOLOv5 model. First, the YOLOv5 model was improved by using the Coordinate attention (CA) module and the regression loss function of boundary box to detect and accurately count the pod targets on the living plants. Then, the prediction model was established to reliably estimate the yield of the whole soybean plant based on Back Propagation (BP) neural network with the topological structure of 5-120-1. The results showed that the average precision (AP) value of the improved YOLOv5 model reached 91.7% with detection rate of 24.39 frames per millisecond. Compared with the traditional YOLOv5 model, the calculation and parameters of the proposed model were reduced by 17% and 7.6%, respectively. The Mean Square Error (MSE) of the estimation for single pod weight was 0.00865, and the average coefficients of determination R2 between predicted and actual weight of a single pod was 0.945. The Mean Relative Error (MRE) of the total weight estimation for all potted soybean plant was 0.122. The proposed method can provide technical support for not only the research and development of the pod’s real-time detection system, but also the intelligent breeding and yield estimation.